1993
DOI: 10.1128/iai.61.5.2270-2272.1993
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxis of leptospires to hemoglobin in relation to virulence

Abstract: A guinea pig-lethal line of Leptospira interrogans serovar copenhageni strain Shibaura, but not an avirulent line of the same strain, moved in larger numbers toward hemoglobin than toward distilled water (control) in a U-shaped polypropylene tube. L. interrogans serovar lai strains 017 and KH-1, which were also guinea pig lethal, showed a similar move to hemoglobin. No such move toward hemoglobin was shown by 14 avirulent strains of L. interrogans (with one exception) or any of the 8 strains of L. bi#exa teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…Virulence can be restored before the irreversible loss by inoculating susceptible animals such as young guinea pigs (14). Hemolysins such as sphingomyelinase C have been previously purified (6) and the corresponding genes have been sequenced (41), but their involvement in pathogenesis is still unclear, even though chemotaxis of pathogenic leptospires to hemoglobin was recently described (46). Attachment of Leptospira to eukaryotic cells, suggesting a relationship between virulence and adhesion in pathogenic leptospires, has been investigated in L929 fibroblastic cells (43) and renal epithelial cells (3).…”
Section: Invasiveness Of Virulent Leptospires Was Significantly Inhibmentioning
confidence: 99%
“…Virulence can be restored before the irreversible loss by inoculating susceptible animals such as young guinea pigs (14). Hemolysins such as sphingomyelinase C have been previously purified (6) and the corresponding genes have been sequenced (41), but their involvement in pathogenesis is still unclear, even though chemotaxis of pathogenic leptospires to hemoglobin was recently described (46). Attachment of Leptospira to eukaryotic cells, suggesting a relationship between virulence and adhesion in pathogenic leptospires, has been investigated in L929 fibroblastic cells (43) and renal epithelial cells (3).…”
Section: Invasiveness Of Virulent Leptospires Was Significantly Inhibmentioning
confidence: 99%
“…For example, in the chemotaxis of S. enterica serovar Typhimurium, most amino acids, including serine and aspartate, can induce an attractive response (Melton et al, 1978), whereas phenol and acetate act as repellents (Tsang et al, 1973). In Leptospira, haemoglobin is an attractant for pathogenic strains but not for saprophytic strains (Yuri et al, 1993). This suggests that pathogenic strains can sense haemoglobin exuding from a break in the host's skin.…”
Section: Introductionmentioning
confidence: 99%
“…Spirochaeta aurantia is attracted to a number of different sugars and is aerotactic (15), whereas acids, alcohols, and sulfides were effective chemorepellants (20). Recently, Yuri et al (38) have demonstrated chemotaxis of virulent leptospires, but not avirulent strains, towards hemoglobin.…”
mentioning
confidence: 99%